Co-Existence of Two Rare Entities in the Male Breast: Intraductal Papilloma and Angiolipoma - Baykara, Murat; Balta, Hilal; Ozcan, Erhan Cahit (Galenos Publ House, 2022)
Intraductal papilloma and angiolipoma lesions are very rare in male breasts and gynecomastia is the most common male breast pathology.A 52-year-old healthy Caucasian male patient with right nipple pain for one month and two subareolar and periareolar masses had no other abnormal clinical or laboratory findings. After ultrasound examination, pull-through excision was made with a circumareolar incision in both lesions and the samples were sent for pathological examination. Histopathological examination revealed intraductal papilloma and angiolipoma on the basis of gynecomastia.This case is unique because both lesions are extremely rare and this is the first report of concurrent occurrence in a male breast.
Keywords: Papilloma; intraductal; angiolipoma; gynecomastia; male; breast